The influence the surface of ventilation duct on sound attenuation in the airflow - Kopania, Joanna Maria; Wójciak, Kamil; Gaj, Patryk; Bogusławski, Grzegorz (Archives of Acoustics, 2026)
These studies focus on acoustical parameters of steel flat-oval ducts in dependence on their roughness. The four types of steel ducts were measured: raw steel, galvanised steel, painted steel, and aluminium as the reference one. The roughness of the duct was measured, and roughness parameters were specified. The sound power level was obtained on the specially constructed stand test with an outlet to the reverberation room. Insertion loss to evaluate the acoustic attenuation performance of the studied steel ducts was obtained. In the present study, an aluminium duct, which is very smooth with minimal airflow friction, was treated as a low-noise object (“silencer”). These studies have shown that for each of the tested steel ducts, the self-noise is higher than for the aluminium duct. The largest differences in this self-noise were observed at a velocity of 12 m/s for the galvanised duct and the raw steel duct compared to the aluminium duct. Insertion losses in straight ducts are consistent with literature and are very low for flat-oval steel ducts. Aluminium duct performs better acoustically than the other ducts studied at lower velocities; however, as airflow velocity increases, the differences in acoustic performance between the materials become less pronounced. That suggests that aerodynamic effects dominate over material surface treatments at higher velocities.